Effects of the controllable mesostructure of nano-sized ZSM-5 on the co-cracking of phenolic bio-oil model compounds and ethanol. Issue 13 (17th June 2019) - Wang, Wenbo; Luo, Zhongyang; Li, Simin; Xue, Shuang; Yang, Yi
Abstract : The mesopore shape and distribution of mesostructured ZSM-5 showed a major influence on aromatics production of co-cracking of phenolic bio-oil and ethanol. Abstract : The textural properties of zeolite catalysts have great influence on the aromatics production during co-cracking of phenolic bio-oil and hydrogen donors, such as ethanol. Through a generalized hydrothermal treatment mediated by ammonia, a series of micron or nano-ZSM-5 with different mesostructure distributions could be easily obtained. The major products of co-cracking with ethanol were analyzed in detail along with structural parameters and acidity properties of the corresponding catalysts. Nanoparticle sizes can effectively increase the cracking performance, especially promoting methoxyl removal. By introducing mesopores into ZSM-5, the co-cracking performance was altered significantly and no longer had good correlation with the concentration of acid sites. The topological shape and position of mesopores had a bigger effect, and the ordered mesopores on the outer surface along with internal mesopores with wide openings were more favorable than hollow mesopores inside with narrow openings. This tendency towards mesopore morphology can be quantified by several structural parameters. Between three kinds of mesostructure distribution, the core–shell ZSM-5 showed optimal performance with the highest BTEX yield and deoxygenation efficiency, due to its improved diffusion of reactants and intermediates. This result can provide reference for the forthcoming design of microporous–mesoporous composite zeolites with more highly ordered mesoporosity for the severe coke deposition reaction.